The Devoicing Intensity of Vowels [I] and [Æœ] in Japanese Language - Siti Muharami Malayu; Muliadi, Yuddi Adrian (Talenta Publisher, 2019)
The research analyzed the intensity of devoicing vowels [i] and [É¯] in Japanese language by its learners. The research used theory of Accoustic Phonetics with Praat Program to measure the intensity of vowels [i] and [É¯]. It analyzed 6 target words uttered by two Japanese Language Learners. A native Japanese speaker was used as the utterance model. It began with recording the voice of the learners in Medan. The research problem was how the intensity of the devoicing of vowels [i] and [É¯] in the first syllable uttered by Japanese Language learners in Medan. The findings, based on Praat analysis with intensity measurement, showed that the intensity of the devoicing of vowels [i] and [É¯] in the first syllable uttered by the four Japanese Language learners was not maximal.